Quality of Life Development of the Elderly Having the Potential to Be Self-reliant in Bangkok Metropolitan - Silawiserit, Ratchaphon; Kalyanamitra, Kamolporn; Niyomyaht, Satit; Lakkanapichonchat, Tassanee (Journal of Thammawat, 2025)
The purpose of this article was: 1) to evaluate the quality of life development of the elderly’s potential being self-sufficient 2) to study the problems and obstacles of the quality of life development of the elderly’s potential being self-sufficient, and 3) to offer the quality of life development of the elderly’s potential being self-sufficient in Bangkok Metropolitan. The research was qualitative. Key informants included executives and government personnel who were involved in the development of the elderly in Bangkok Metropolitan, president of the Elderly Club and self-reliant elderly people totaling 20 key informants, by a purposive selection. The research tool was a structured interview form. Data were analyzed by a descriptive summary. The research revealed that: 1) Efforts to enhance the quality of life for the elderly involve promoting self-reliance through various means such as promoting self-care, preventing illnesses, developing healthcare systems, using various media to disseminate necessary knowledge and information, managing necessary teaching and training skills, promoting employment and income opportunities in various forms, increasing social roles for the elderly, raising awareness of the importance of the elderly, and improving residential facilities and physical environments conducive to the elderly. 2) Challenges in improving the quality of life for the elderly include limited budgets, restricted personnel, lack of knowledge and understanding about the elderly, insufficient appreciation of the value and importance of the elderly, health problems among the elderly, and inadequate promotion of suitable employment opportunities. 3) Recommendations for enhancing the self-reliance of the elderly in Bangkok include developing public health management mechanisms, supporting elderly employment, promoting professional skill development, creating elder-friendly community environments, improving suitable housing, and fostering positive attitudes towards the elderly in society.